PERANCANGAN APLIKASI MONITORING PENGIRIMAN BARANG BERBASIS WEB PADA PT.JOS - Putri Agustin; Thomas Budiman; Anton Zulkarnain Sianipar (Universitas Serang Raya, 2025)
The smoothness of the goods delivery process is a crucial factor in supporting the operational effectiveness of a distribution company. PT. Jaka Oetama Sentosa (PT. JOS) currently still applies manual coordination between warehouses, which causes delays in information, risks of recording errors, and reduces work efficiency. This study aims to design and develop a web-based goods delivery monitoring application that is used internally to improve transparency and accuracy of shipping information. The research method used is Rapid Application Development (RAD), with data collection through direct observation, interviews with users, and literature studies. The results of the study include user interface design, database development, and implementation of an integrated system. The implementation of this application is expected to accelerate the delivery of information, reduce recording errors, and increase the effectiveness of monitoring the goods distribution process at PT. JOS. These findings provide a significant contribution to optimizing the distribution process through internal company digitalization. Keywords: Design, Application, Monitoring, Goods Delivery, Website, Rapid Application Development.